Spray-Dried Porcine Plasma Promotes the Association Between Metabolic and Immunological Processes at Transcriptional Level in Gilthead Sea Bream (Sparus aurata) Gut - Vallejos-Vidal, Eva; Reyes-Cerpa, Sebastián; Tort, Lluis; Polo, Javier; Reyes-López, Felipe E.; Gisbert, Enric (Frontiers in Marine Science, 2022)
The spray-dried porcine plasma (SDPP) is an abattoir by-product used in animal nutrition with beneficial effects reported in livestock and commercial aquatic species. Previous results have found that the dietary inclusion of SDPP in gilthead sea bream (Sparus aurata) increased the density of intestinal goblet cells and it did not result in major changes in the autochthonous microbiota. However, there is no comprehensive data on the mechanisms that could take place on the intestine of gilthead sea bream fed with SDPP-supplemented diet. For this reason, the aim of this study was to unveil the biological mechanisms modulated in response to the dietary administration of SDPP in the gilthead sea bream gut. To achieve this goal, we made a microarrays-based transcriptomic approach in gut samples from gilthead sea bream fed with SDPP-supplemented diet for 95 days. As control diet, we used a protein-rich commercial feed (51% crude protein, 17% crude fat and 20.6 MJ/kg gross energy), that it was supplemented with 3% SDPP at the expense of LT70 fishmeal. The microarray analyses showed a total of 803 (468 up- and 335 down-regulated) differential expressed genes (DEGs). The functional network analysis revealed that dietary inclusion of SDPP induced sustained changes in 120 biological processes, grouped in 12-clusters. Among them, the metabolic-related process (cellular catabolic process, organic substance catabolic process, protein metabolism process), protein transport, and leukocyte mediated immunity were interacting in the main interactome network. This evidence confirms the previous evidence of the enhancement of the mucosal health status in response to the dietary administration of SDPP and provides further understanding on the mode of action of this ingredient in aquafeeds.